Characteristics of Publicly Insured Children with High Dental Expenses - Shervin S. Churchill, MPH; Bryan J. Williams, DDS; Nanci L. Villareale, MSN (Blackwell Synergy, 2007)
Dental coverage is provided for all children with Medicaid in Washington State. The goal of this study was to illuminate the characteristics of a sample of Medicaid-enrolled children with high dental expenses.